Detection of Carp pox virus (CyHV-1) from koi (Cyprinus carpio L.) in Iran; clinico-pathological and molecular characterization. (December 2020) - Rahmati-Holasoo, Hooman; Ahmadivand, Sohrab; Shokrpoor, Sara; El-Matbouli, Mansour
Abstract: Cyprinid herpesvirus 1 (CyHV-1) is the causative agent of carp pox characterized by epidermal papillomas in common carp and other cyprinids. In this study, we identified CyHV-1 in koi ( Cyprinus carpio ) from Iran in 2017 and 2019, showing clinical signs of the carp pox disease. Histopathology showed severe epidermal hyperplasia and the absence of club and goblet cells. Degenerative changes, including spongiosis and single-cell necrosis, were also observed. Keratinocyte dysplasia and a moderate lymphocytic infiltration were observed within the epidermis. PCR of the extracted DNA from skin lesions of affected koi from both outbreaks showed CyHV-1 specific TK amplicons, with high sequence identity (above 99%) among themselves and with other CyHV-1 isolates belong to Cluster I, as well as show 97% similarity to Cluster II isolates. To the best of our knowledge, this is the first report of Carp pox disease (CyHV-1) of koi in Iran and the Middle East. Highlights: This is the first report of Carp pox virus (CyHV-1) from koi in Iran. Diagnosis of CyHV–1 was made by clinical, histopathological, and molecular characterization. The isolates have been detected using the TK gene-based PCR assay. We have classified the CyHV–1 isolates in to Cluster I (I-a and I-b) and Cluster II based on TK gene. The Iranian CyHV–1 isolates were classified as Cluster I.